Impact of EU regulatory label changes for diclofenac in people with cardiovascular disease in four countries: Interrupted time series regression analysis. Issue 3 (2nd August 2020) - Morales, Daniel R.; Morant, Steven V.; MacDonald, Thomas M.; Hallas, Jesper; Ernst, Martin Thomsen; Pottegard, Anton; Herings, Ron M.C.; Smits, Elisabeth; Overbeek, Jetty A.; Mackenzie, Isla S.; Doney, Alexander S.F.; Mitchell, Lyn; et al.
Abstract : Objective: Due to cardiovascular safety concerns, the European Medicines Agency (EMA) recommended new contraindications and changes to product information for diclofenac across Europe in 2013. This study aims to measure their impact among targeted populations. Method: Quarterly interrupted time series regression (ITS) analyses of diclofenac initiation among cohorts with contraindications (congestive cardiac failure [CHF], ischaemic heart disease [IHD], peripheral arterial disease [PAD], cerebrovascular disease [CVD]) and cautions (hypertension, hyperlipidaemia, diabetes) from Denmark, the Netherlands, England and Scotland. Results: The regulatory action was associated with significant immediate absolute reductions in diclofenac initiation in all countries for IHD (Denmark −0.08%, 95%CI −0.13, −0.03; England −0.09%, 95%CI −0.13 to −0.06%; the Netherlands −1.84%, 95%CI −2.51 to −1.17%; Scotland −0.34%, 95%CI −0.38 to −0.30%), PAD and hyperlipidaemia, the Netherlands, England and Scotland for hypertension and diabetes, and England and Scotland for CHF and CVD. Post‐intervention there was a significant negative trend in diclofenac initiation in the Netherlands for IHD (−0.12%, 95%CI −0.19 to −0.04), PAD (−0.13%, 95%CI −0.22 to −0.05), hypertension, hyperlipidaemia and diabetes, and in Scotland for CHF (−0.01%, 95%CI −0.02 to −0.007%), IHD (−0.017, 95%CI −0.02, −0.01%), PAD and hypertension. In England, diclofenac initiation rates fell less steeply. In Denmark changes were more strongly associated with the earlier EMA 2012 regulatory action. Conclusion: Although significant reductions in diclofenac initiation occurred, patients with contraindications continued to be prescribed diclofenac, the extent of which varied by country and target condition. Understanding reasons for such variation may help to guide the design or dissemination of future safety warnings.